A computerized tomographic study of height of ethmoidal skull base - N, Vinay Kumar; TS, Gugapriya; Guru, Arun T.; SD, Nalinakumari (International Journal of Clinical Trials, 2014)
Background: During Endoscopic Sinus Surgeries (ESS), the most important anatomical structures that need preoperative visualisation and evaluation are the lateral lamella and ethmoidal skull base as many reports of complications due to injury of these structures exist. Ethmoidal Skull Base (ESB) extends from the superior attachment of lateral lamella of cribriform plate to the junction of the lamina papyracea. The aim is to study and evaluate ESB using coronal sinus CT images. Methods: Sixty coronal sinus CT scan images at the level of visualization of anterior ethmoidal artery canal were taken for studying the ESB on both sides. A horizontal line bisecting the orbit was taken as the base line reference for inferior extent. The height of the ESB was measured and classified into high, moderate and low ESB by taking 7 mm as upper limit and 4 mm as lower limit. Mean height of ESB in the study group was computed and its difference among gender and sides were noted and statistically analysed. Results: ESB varied between 3.7 mm to 15.4 mm with mean height of 10.05 mm. Low ESB was found only in females and there was no statistically significant side asymmetry of ESB height. Conclusions: Preoperative recognition of low ESB and alerting the surgeon of the potential for iatrogenic injury by measuring the height of ESB needs to become a standard practice in order to minimize the complications during ESS.